Hygrothermal performance of rammed earth wall in Tibetan Autonomous Prefecture in Sichuan Province of China. (15th August 2020) - Jiang, Bin; Wu, Tao; Xia, Wenjing; Liang, Jiahua
Abstract: Building construction accounts for 40% of the global anthropogenic greenhouse gas emissions. The drastic increase in the energy costs of building materials has drawn attention to earth materials, such as rammed earth. In this study, the hygrothermal properties of rammed earth in the Tibetan Autonomous Prefecture, Sichuan Province, China were measured and compared with results from previous studies. To analyze the hygrothermal performance of a rammed earth wall, a numerical model was established and verified. The coupled heat and moisture transfer in the area of the common rammed earth wall and the moisture barrier wall was simulated with different indoor conditions, orientations, and thicknesses. The numerical results were observed to be consistent with the experimental data. In contrast to results from other studies, the earthen material analyzed in this study exhibits less vapor transfer, but better thermal stability and moisture buffering. The moisture barrier increases the average moisture content of the rammed earth wall, but reduces the maximum moisture content, thereby protecting the wall. The moisture barrier probably also reduces the moisture buffering capacity of the wall. The moisture barrier has no significant effect on heat transfer; even a west-facing wall reduces heat loss by only 3% in this area. Highlights: The studied earthen material has lower diffusivity and higher effusivity. The moisture barrier results in a maximum reduction in moisture transfer of 35%. The increase of moisture transfer reduces the heat loss of the wall for the whole year. The moisture barrier will be more effective used on rammed earth wall facing west.